Evidence for high‐temperature fractionation of lithium isotopes during differentiation of the Moon. (17th April 2016) - Day, James M. D.; Qiu, Lin; Ash, Richard D.; McDonough, William F.; Teng, Fang‐Zhen; Rudnick, Roberta L.; Taylor, Lawrence A.
Abstract: Lithium isotope and abundance data are reported for Apollo 15 and 17 mare basalts and the LaPaz low‐Ti mare basalt meteorites, along with lithium isotope data for carbonaceous, ordinary, and enstatite chondrites, and chondrules from the Allende CV3 meteorite. Apollo 15 low‐Ti mare basalts have lower Li contents and lower δ 7 Li (3.8 ± 1.2‰; all uncertainties are 2 standard deviations) than Apollo 17 high‐Ti mare basalts (δ 7 Li = 5.2 ± 1.2‰), with evolved LaPaz mare basalts having high Li contents, but similar low δ 7 Li (3.7 ± 0.5‰) to Apollo 15 mare basalts. In low‐Ti mare basalt 15555, the highest concentrations of Li occur in late‐stage tridymite (>20 ppm) and plagioclase (11 ± 3 ppm), with olivine (6.1 ± 3.8 ppm), pyroxene (4.2 ± 1.6 ppm), and ilmenite (0.8 ± 0.7 ppm) having lower Li concentrations. Values of δ 7 Li in low‐ and high‐Ti mare basalt sources broadly correlate negatively with 18 O/ 16 O and positively with 56 Fe/ 54 Fe (low‐Ti: δ 7 Li ≤4‰; δ 56 Fe ≤0.04‰; δ 18 O ≥5.7‰; high‐Ti: δ 7 Li >6‰; δ 56 Fe >0.18‰; δ 18 O <5.4‰). Lithium does not appear to have acted as a volatile element during planetary formation, with subequal Li contents in mare basalts compared with terrestrial, martian, or vestan basaltic rocks. Observed Li isotopic fractionations in mare basalts can potentially be explained through large‐degree, high‐temperature igneous differentiation of their source regions. Progressive magma ocean crystallization led to enrichment in Li and δ 7 Li in late‐stage liquids, probably as a consequence of preferential retention of 7 Li and Li in the melt relative to crystallizing solids. Lithium isotopic fractionation has not been observed during extensive differentiation in terrestrial magmatic systems and may only be recognizable during extensive planetary magmatic differentiation under volatile‐poor conditions, as expected for the lunar magma ocean. Our new analyses of chondrites show that they have δ 7 Li ranging between −2.5‰ and 4‰. The higher δ 7 Li in planetary basalts than in the compilation of chondrites (2.1 ± 1.3‰) demonstrates that differentiated planetary basalts are, on average, isotopically heavier than most chondrites.